2022
DOI: 10.3847/1538-4357/ac5d5b
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Coupling of Streamers and Pseudostreamers to the Heliosphere

Abstract: The slow solar wind is generally believed to result from the interaction of open and closed coronal magnetic flux at streamers and pseudostreamers. We use three-dimensional magnetohydrodynamic simulations to determine the detailed structure and dynamics of open-closed interactions that are driven by photospheric convective flows. The photospheric magnetic field model includes a global dipole giving rise to a streamer together with a large parasitic polarity region giving rise to a pseudostreamer that separates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Since there has been recent progress integrating aspects of heavy ion composition forward modeling into steady-state MHD solar wind calculations (e.g., Oran et al 2015;Shen et al 2017;Lionello et al 2019;Szente et al 2022), it would be extremely interesting to perform these calculations on dynamic, time-dependent MHD modeling of the formation and evolution of coherent magnetic structures generated under different reconnection scenarios. For example, the Aslanyan et al (2022) calculation of the synthetic suprathermal electron PAD "time series" associated with PS interchange reconnection outflows shows excellent qualitative agreement with the observed broadening of the strahl for some of our PS intervals (#4, #6, and #7 in particular). Lynch et al (2014) showed the largest (i.e., low-frequency) δB/〈B〉 signatures resulting from PS reconnection had characteristic length scales of 100-350 Mm (0.14-0.50 R e ) in the corona, which reflected the spatial scale of their PS flux system of origin, and Higginson & Lynch (2018) demonstrated that the MHDsimulation-derived, synthetic in situ magnetic field signatures of a similarly sized, nonlinear torsional Alfvén wave could resemble the coherent magnetic structure of small-scale magnetic flux ropes/streamer blob plasmoids typically associated with HS slow wind in the vicinity of the HCS/HPS.…”
Section: Summary and Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Since there has been recent progress integrating aspects of heavy ion composition forward modeling into steady-state MHD solar wind calculations (e.g., Oran et al 2015;Shen et al 2017;Lionello et al 2019;Szente et al 2022), it would be extremely interesting to perform these calculations on dynamic, time-dependent MHD modeling of the formation and evolution of coherent magnetic structures generated under different reconnection scenarios. For example, the Aslanyan et al (2022) calculation of the synthetic suprathermal electron PAD "time series" associated with PS interchange reconnection outflows shows excellent qualitative agreement with the observed broadening of the strahl for some of our PS intervals (#4, #6, and #7 in particular). Lynch et al (2014) showed the largest (i.e., low-frequency) δB/〈B〉 signatures resulting from PS reconnection had characteristic length scales of 100-350 Mm (0.14-0.50 R e ) in the corona, which reflected the spatial scale of their PS flux system of origin, and Higginson & Lynch (2018) demonstrated that the MHDsimulation-derived, synthetic in situ magnetic field signatures of a similarly sized, nonlinear torsional Alfvén wave could resemble the coherent magnetic structure of small-scale magnetic flux ropes/streamer blob plasmoids typically associated with HS slow wind in the vicinity of the HCS/HPS.…”
Section: Summary and Discussionsupporting
confidence: 67%
“…With the inclusion of the magnetic field and suprathermal electron PAD, the intervals corresponding to sector boundaries and heliospheric current sheet/plasma sheet (HCS/HPS) crossings are immediately apparent as #8 and #3, both shaded light yellow.Another particularly noteworthy feature of Figure3is that each of the remaining slow-to-moderate speed intervals are coincident with broader suprathermal electron PADs and/or elevated charge states in carbon, oxygen, and iron. While recent analyses byBorovsky (2020Borovsky ( , 2021 have shown that changes in the suprathermal electron strahl intensities often occur with simultaneous changes in other plasma and/or composition properties, here we note that the broader PADs of intervals #7, #6, and #4 exhibit remarkable, qualitative agreement with the synthetic PAD distribution constructed byAslanyan et al (2022) from their MHD simulation of…”
supporting
confidence: 77%
See 2 more Smart Citations